An Exploratory Study of Translational Norms in Simultaneous Interpreting: Methodological Reflections - Schjoldager, Anne (HERMES - Journal of Language and Communication in Business, 2017)
This paper discusses some possibilities that the theory of translational norms (Toury 1980) may offer in connection with research into simultaneous interpreting. After a brief discussion of the concept of translational norms, I explore how this concept may be useful in interpreting research in general. I then proceed to discuss and criticize the set-up of my own project on simultaneous interpreting and translation - especially how progressive aspect was originally used as a focus of analysis. I conclude by demonstrating how the theory of translational norms has been a useful methodological tool in the analysis of my data. One result is the discovery that certain translational norms seem to be peculiar to simultaneous interpreting - for instance norms regarding what one ought to do in connection with capacity saturation.